Unconventional application of the Mitsunobu reaction: Selective flavonolignan dehydration yielding hydnocarpins - Huang, Guozheng; Schramm, Simon; Heilmann, Jörg; Biedermann, David; Křen, Vladimír; Decker, Michael (Beilstein journal of organic chemistry, 2016)
Various Mitsunobu conditions were investigated for a series of flavonolignans (silybin A, silybin B, isosilybin A, and silychristin A) to achieve either selective esterification in position C-23 or dehydration in a one-pot reaction yielding the biologically important enantiomers of hydnocarpin D, hydnocarpin and isohydnocarpin, respectively. This represents the only one-pot semi-synthetic method to access these flavonolignans in high yields.
Keywords: flavonoid; silybin; Mitsunobu; dehydration; hydnocarpin